Emerging from the Shadows: Recognizing John Norton - Finlayson, Alan (Ontario History)

(untitled) (The Ontario Historical Society, 2018)
John Norton (Teyoninhokaren) lived a multi-faceted life as diplomat, political leader, war chief, and author. Famous in his day and seen as “extraordinary” by contemporaries, he remained in the shadows of Tecumseh and Joseph Brant because of a lack of information and the negative portrayals of him by his adversaries. With the discovery of his personal correspondence and Journal, his character has been re-evaluated and his significance as a leader of the Six Nations, an important war chief in the War of 1812, and an author and historian, recognized. As well, his connections with Canada’s first internationally acclaimed author, Major John Richardson has been acknowledged and Norton recognized as a model for the character “Wacousta.” Little focus has been made of his “Wacousta” connection and an updated “overview” of his career has not appeared. Given his new status and what we now know of him, he is deserving of greater recognition and a fuller and up-to-date portrayal.